Unsteady MHD Mixed Convection Flow of Chemically Reacting Micropolar Fluid between Porous Parallel Plates with Soret and Dufour Effects - Odelu Ojjela; N. Naresh Kumar (Journal of Engineering)
The objective of the present study is to investigate the first-order chemical reaction and Soret and Dufour effects on an incompressible MHD combined free and forced convection heat and mass transfer of a micropolar fluid through a porous medium between two parallel plates. Assume that there are a periodic injection and suction at the lower and upper plates. The nonuniform temperature and concentration of the plates are assumed to be varying periodically with time. A suitable similarity transformation is used to reduce the governing partial differential equations into nonlinear ordinary differential equations and then solved numerically by the quasilinearization method. The fluid flow and heat and mass transfer characteristics for various parameters are analyzed in detail and shown in the form of graphs. It is observed that the concentration of the fluid decreases whereas the temperature of the fluid enhances with the increasing of chemical reaction and Soret and Dufour parameters.